2019
DOI: 10.1002/celc.201901293
|View full text |Cite
|
Sign up to set email alerts
|

Collapse‐Resistant Large‐Sized 2D Metal‐Organic‐Framework‐Derived Nitrogen‐Doped Porous Ultrathin Carbon Nanosheets for High‐Performance Supercapacitors

Abstract: Metal‐organic‐framework (MOF)‐derived two‐dimensional materials have attracted tremendous attention in energy storage, because of their unique layered structure and abundant active sites. However, the facile synthesis of carbon materials simultaneously having large‐sized, ultrathin‐layered nanosheets and ultrahigh specific surface area remains a challenge. In this work, we develop a simple carbon protection strategy for efficiently stabilizing the ultrathin carbon nanosheets against structure degradation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This hierarchical porous structure with abundant structure defects not only facilitates the mass transport of ions but also enhances the ability of carbon for the ion adsorption. 31 To investigate the activation effect of KOH on the pore structure, the N 2 adsorption−desorption method was also performed (Figure 2a,b). As shown in Figure 2a and Figure S4, the nitrogen adsorption−desorption isotherm of HPC-K6 exhibits both characteristics of type I (the sharp increase at low relative pressure indicating rich micropores) and type IV (an obvious hysteresis loop at the middle relative pressure indicating the existence of mesopores) according to the IUPAC classification, 32,33 suggesting a well-developed hierarchical porous structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hierarchical porous structure with abundant structure defects not only facilitates the mass transport of ions but also enhances the ability of carbon for the ion adsorption. 31 To investigate the activation effect of KOH on the pore structure, the N 2 adsorption−desorption method was also performed (Figure 2a,b). As shown in Figure 2a and Figure S4, the nitrogen adsorption−desorption isotherm of HPC-K6 exhibits both characteristics of type I (the sharp increase at low relative pressure indicating rich micropores) and type IV (an obvious hysteresis loop at the middle relative pressure indicating the existence of mesopores) according to the IUPAC classification, 32,33 suggesting a well-developed hierarchical porous structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Simultaneously, mesopores favor the rapid ion diffusion, and the extra macropores in the material can offer an ion-buffering effect to shorten the ion diffusion distance. This hierarchical porous structure with abundant structure defects not only facilitates the mass transport of ions but also enhances the ability of carbon for the ion adsorption …”
Section: Resultsmentioning
confidence: 99%
“…To address these problems, extensive electrode materials of different dimensions including 0D quantum dots, [ 12 ] 1D nanotubes and graphene nanoribbons, [ 13–15 ] nanowires and nanorods, [ 16,17 ] 2D nanosheets, [ 18 ] etc., have sprung up. Among these materials, 2D materials such as graphene and graphene oxide (GO), [ 19 ] MXene, [ 20 ] transition metal dichalcogenides, [ 21 ] transition metal oxides (TMOs), [ 22 ] and black phosphorus (BP) [ 23 ] have been widely used in flexible and miniaturized wearable electronic devices due to their accessible active sites, shortened ion transfer distance, excellent mechanical strength and flexibility caused by in‐plane covalent bonds, and inter‐layer van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22] Remarkably, it has been demonstrated that the existence of two-dimensional structure in hybrid composites is capable to improve the effective contact between end members, facilitating the transport of electrons and ions during the electrochemical reaction. [23][24][25] For instance, Y.C. Jiang et al proposed a facile insitu nucleation strategy to immobilize monodispersed Ni-Fe LDH ultrafine nanosheets on graphene oxide.…”
Section: Introductionmentioning
confidence: 99%
“… 14–22 Remarkably, it has been demonstrated that the existence of two-dimensional structures in hybrid composites can improve the effective contact between end members, facilitating the transport of electrons and ions during the electrochemical reaction. 23–25 For instance, Y. C. Jiang et al proposed a facile in situ nucleation strategy to immobilize monodispersed Ni–Fe LDH ultrafine nanosheets on graphene oxide. 26 The composited Ni–Fe LDH@rGO electrode, which was regarded as a microreactor, could provide high specific capacitances and energy densities.…”
Section: Introductionmentioning
confidence: 99%